Thermophoresis and Brownian motion effects on unsteady MHD nanofluid flow over a slendering stretching surface with slip effects - J.V. Ramana Reddy; V. Sugunamma; N. Sandeep (Alexandria Engineering Journal, 2018)
In the current exploration, a similarity solution is bestowed for hydromagnetic motion of a nanofluid over a slendering stretching sheet with the existence of thermophoresis and Brownian moment. We first altered the time dependent governing mathematical equations into coupled dimensionless differential equations by making use of apposite transmutations. Numerical solution for these equations is procured deploying R.K.-Fehlberg numerical methodology. Further, the impacts of sundry non-dimensional parameters on the flow field along with shear stress, reduced heat and mass transfer have been tackled with the succor of plots and tabular forms. It is worth to divulge that an upturn in the magnitude of thermophoretic and Brownian motion parameters amplifies the fluid temperature, whereas the concentration profiles get depreciated with a hike in thermophoretic parameter. Keywords: MHD, Thermophoresis, Brownian motion, Slendering stretching sheet, Slip effects